Analysis of the Structural Design of Betang Houses in Central Kalimantan for Cultural Heritage Preservation and Local Tourism Potential - Ilas, Yunanae Eka Asi; Burako, Miming Virganinda; Happy, Yanshon (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This research investigates the structural design of Betang houses in Central Kalimantan and their potential for cultural heritage preservation and local tourism development. Betang houses, traditional dwellings of the Dayak Ngaju people, have become significant cultural landmarks with both historical and architectural value. This study applies qualitative research through field observations, interviews, and literature review to analyze the architectural elements and preservation strategies of Betang Toyoi in Tumbang Malahoi Village, Gunung Mas Regency. The results highlight the unique architectural features of the Betang, including its robust wooden pillars, intricate roof structure, and symbolic elements. Additionally, the study explores the potential of Betang houses to attract tourists, offering insights into the economic opportunities related to cultural heritage tourism. Despite the potential, the research indicates that suboptimal management and maintenance have hindered the full realization of Betang Toyoi’s tourism potential. The study concludes by emphasizing the need for improved infrastructure, support from local government, and enhanced management strategies to optimize the economic and cultural contributions of the Betang houses. These findings underscore the importance of preserving traditional architecture as part of the region’s cultural heritage and sustainable tourism development.